Demographic change in the Upper Tsitsa Catchment: the integration of census and land cover data for 2001 and 2011 - Hodgson, Danuta Lorina (Rhodes University, Faculty of Science, Department of Geography, 2018)
The purpose of this research was to determine if the integration of census and land cover data could provide evidence of spatial patterns and temporal change for the Upper Tsitsa Catchment. This thesis contributed to academic literature with regards to dasymetric mapping and provided a database for the Ntabelanga and Laleni Ecological Infrastructure Project. The study took place in the Upper Tsitsa Catchment which is located in the north-eastern region of the Eastern Cape and falls within the uMzimvubu Catchment. South Africa National Population Censuses for 2001 and 2011 and the National Land Cover data sets for 2000 and 2013/14 were used to create dasymetric maps depicting demographic changes over time for the catchment area. Spatial statistics were performed on the dasymetric and choropleth map to determine the accuracy of the data that was created. From the results, it was found that although the statistics were skewed, the method was more accurate in displaying the population densities, which was noted during the sampling process of the spatial analysis. It was found that there had been a decrease in the population density within the catchment. This affected the density of several other variables such as population race group, language and employment status statistics as decreases in these values could be due to individuals migrating out of the catchment as well as socio-economic upliftment, such as having better access to services. The use of dasymetric mapping allowed an accurate representation of the population density from the census data to be created. The results of the dasymetric mapping were more accurate as they depicted where the population within the enumeration areas were located, and recognised that some areas were populated while some areas were not. To conclude, it was found that using dasymetric mapping provided reliable and useful data about population density and enables comparison over time.
Keywords: Land use -- South Africa -- Eastern Cape; Watersheds -- South Africa -- Eastern Cape; Thematic maps -- South Africa -- Eastern Cape; Population density -- South Africa -- Eastern Cape; Mzimvubu River Watershed (South Africa) -- Census; Upper Tsitsa Catchment (South Africa)